APLIKASI REKAYASA NILAI (STUDI KASUS : PROYEK JALAN TOL SEMARANG – SOLO RUAS SEMARANG – BAWEN SESI PENGGARON – BEJI) - Weny Saputri; Saut Martua Hasiholan Saragih; Mochammad Agung Wibowo; Bagus Hario Setiadji (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The increasing of Indonesian population growth resulted the requirement of society in a whole aspects of life increase, including the requirement on transportation. Semarang-Solo highways is one of the thoroughfare in Central Java, the volume of traffic that increasingly dense making it unable to accommodated by the highway. As a solution, the government through PT. Trans Marga Central Java build a toll road to connects the city of Semarang and Solo along 75.67 km. The development of Semarang-Solo toll road Semarang Bawen segment Penggaron-Bejii section using rigid pavement as early design of pavement. Evaluation results show this design have some weakness, so it needs the innovation of the pavement to minimize the shortage. Through value engineering stage is the stage of information, speculation, analysis, development, presentation and implementation found that alternative designs were selected for use on this highway is a system of precast prestressed concrete pavement (PPCP). Analysis results the system in the design of the project will reduce the execution time for 84 days or 21% of rigid pavement method.